Third molar agenesis as a potential marker for craniofacial deformities - Avelar Fernandez, Clarissa Christina (2018)
The identification of clinical patterns of tooth agenesis in individuals born with craniofacial deformities may be a useful tool for risk determination of these defects. We hypothesize that specific craniofacial deformities are associated with third molar agenesis. Objective: The aim of this study was to identify if third molar agenesis could have a relation with other craniofacial structure alterations, such as cleft lip and palate, skeletal malocclusion, or specific growth patterns in humans. Design: Data were obtained from 550 individuals ascertained as part of studies aiming to identify genetic contributions to oral clefts. 831 dental records of patients aged over eight years seeking orthodontic treatment were also included. SN-GoGn angle were used to classify the growth pattern (hypo-divergent, normal and hyper-divergent), and the ANB angle was used to verify the skeletal malocclusion pattern (Class I, II and III). Panoramic radiographs were used to determine third molar agenesis. Results: A high frequency of third molar agenesis among individuals born with cleft lip with or without cleft palate (55%), as well as among their relatives (93.5%) was found. Third molar agenesis was not associated to skeletal malocclusion or growth pattern. Conclusion: It appears that third molar agenesis is associated with the disturbances that lead to cleft lip and palate.